Multiple Horizontal Transfers of Bacteriophage WO and Host Wolbachia in Fig Wasps in a Closed Community - Wang, Ningxin; Jia, Sisi; Xu, Heng; Liu, Yong; Huang, Dawei (Frontiers in Microbiology, 2016)
Wolbachia-bacteriophage WO is a good model system for studying interactions between bacteria and viruses. Previous surveys of insect hosts have been conducted via sampling from open or semi-open communities; however, no studies have reported the infection patterns of phage WO of insects living in a closed community. Figs and fig wasps form a peculiar closed community in which the Ficus tree provides a compact syconium habitat for a variety of fig wasps. Therefore, in this study, we performed a thorough survey of Wolbachia and bacteriophage WO infection patterns in a total of 1406 individuals from 23 fig wasps species living on three different fig tree species. The infection rates of Wolbachia and phage WO were 82.6% (19/23) and 39.1% (9/23), respectively. Additionally, phage WO from fig wasps showed strong insect host specificity based on orf7 sequences from fig wasps and 21 other insect species. Probably due to the physical barrier of fig syconium, most phage WO from fig wasps form a special clade. Phylogenetic analysis showed the absence of congruence between WO and host Wolbachia, WO and insect host, as well as Wolbachia and fig wasps, suggesting that both Wolbachia and phage WO exchanged frequently and independently within the closed syconium. Thus, the infection pattern of bacteriophage WO from fig wasps appeared quite different from that in other insects living outside, although the effect and the transfer routes of phage WO are unclear, which need to be investigated in the future.